SARS-CoV-2 Omicron sublineages show comparable cell entry but differential neutralization by therapeutic antibodies - Arora, Prerna; Zhang, Lu; Krüger, Nadine; Rocha, Cheila; Sidarovich, Anzhalika; Schulz, Sebastian; Kempf, Amy; Graichen, Luise; Moldenhauer, Anna Sophie; Cossmann, Anne; Dopfer-Jablonka, Alexandra; Behrens, Georg M.N.; et al. (Cell Host & Microbe, 2022)
The Omicron variant of SARS-CoV-2 evades antibody-mediated neutralization with unprecedented efficiency. At least three Omicron sublineages have been identified—BA.1, BA.2, and BA.3—and BA.2 exhibits increased transmissibility. However, it is currently unknown whether BA.2 differs from the other sublineages regarding cell entry and antibody-mediated inhibition. Here, we show that BA.1, BA.2, and BA.3 enter and fuse target cells with similar efficiency and in an ACE2-dependent manner. However, BA.2 was not efficiently neutralized by seven of eight antibodies used for COVID-19 therapy, including Sotrovimab, which robustly neutralized BA.1. In contrast, BA.2 and BA.3 (but not BA.1) were appreciably neutralized by Cilgavimab, which could constitute a treatment option. Finally, all sublineages were comparably and efficiently neutralized by antibodies induced by BNT162b2 booster vaccination after previous two-dose homologous or heterologous vaccination. Collectively, the Omicron sublineages show comparable cell entry and neutralization by vaccine-induced antibodies but differ in susceptibility to therapeutic antibodies.
CRIS-Team Scopus Importer:2022-08-19
Keywords: ACE2; antibody; neutralization; Omicron; SARS-CoV-2; sotrovimab; spike; vaccine